2018
DOI: 10.1101/328765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular determinants of WNT9b responsiveness in nephron progenitor cells

Abstract: Primed nephron progenitor cells (NPCs) appear in metanephric mesenchyme by Ell.5 and differentiate in response to the inductive WNT9b signal from the ureteric bud. However, the NPC WNT-receptor complex is unknown. We obtained M15 cells from E10.5 mesonephric mesenchyme and systematically analyzed components required for canonical WNT9b-responsiveness. When M15 cells were transfected with a (β-catenin luciferase reporter plasmid, exposure to recombinant WNT9b resulted in minimal luciferase activity. We then ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…These findings are consistent with recent in vitro data that described Rspo1 to enhance canonical signalling upon treatment of a mesonephric cell line (M15) with WNT9b (Ref. 33 ). However, at present we can not exclude that R-spondins may also modulate non-canonical WNT signalling, which might affect cell adhesion and migration of NPCs.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with recent in vitro data that described Rspo1 to enhance canonical signalling upon treatment of a mesonephric cell line (M15) with WNT9b (Ref. 33 ). However, at present we can not exclude that R-spondins may also modulate non-canonical WNT signalling, which might affect cell adhesion and migration of NPCs.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with recent in vitro data that described Rspo1 to enhance canonical signalling upon treatment of a mesonephric cell line (M15) with WNT9b (Ref. 31 ).…”
Section: Discussionsupporting
confidence: 93%
“…It has been appreciated for over a decade that a UB-derived Wnt9b canonical signal is required for both maintenance of self-renewal capacity of NPC as well as for their differentiation (Carroll et al, 2005;Karner et al, 2011). Recently, work in cells derived from E10.5 mesonephric mesenchyme identified a role for Rspo1, Lrp6 and Fzd5 in enabling Wnt9b responsiveness as cells transitioned from the intermediate mesoderm to the metanephric mesenchyme identity (Dickinson et al, 2019). It was further demonstrated that low signaling input promotes selfrenewal and high signaling input promotes differentiation (Ramalingam et al, 2018).…”
Section: Discussionmentioning
confidence: 99%